Determinação simultânea de benserazida e l-dopa empregando um eletrodo a base de nanotubo de carbono e diamante dopado com boro - LIMA, Adriano Rogerio Silva (2018)
The present work describes the simultaneous electroanalytical determination of benserazide and L-dopa on boron-doped diamond / Multi-Walled carbon nanotube electrode (BDDMWCNT/Ti) electrode. The electrode has been successfully applied to simultaneous electrochemical oxidation of benserazide and L-dopa, which occurs at 0.150 mV and +0.600 mV vs Ag/AgCl, respectively. The electrochemical and electroanalytical properties of the BDD-MWCNT/Ti electrode were investigated by cyclic voltammetry, electrochemical impedance spectroscopy, scanning electrochemical microscopy, and differential pulse voltammetry. The electrode presented lower electrooxidation potential for both L-dopa and benserazide in 0.1 mol L-1 of phosphate buffer at pH 7.0 while maintaining its high sensitivity. Under optimized conditions, the BDD-MWCNT/Ti electrode presents a linear response range from 40 μmol L-1 to 400 µmol L-1 for L-dopa and from 14 μmol L-1 to 136 µmol L-1 for benserazide. The limit of detection of the proposed sensor for L-dopa and benserazide were 18 μmol L-1 and 1 μmol L-1, respectively. The sensor has been successfully applied for selective determination of L-dopa and benserazide in urine samples and it is very promising for many electroanalytical applications.